Manager’s Leadership Style on Instructors’ Teaching Performance - Nurul Fitriyah Almunawaroh; Dita Rizki Anggraini (J-SHMIC : Journal of English for Academic, 2020)
This study was aimed at finding out the leadership style used by the manager and how it corresponds to the instructors’ teaching performance. The samples were a manager and eight instructors of one of English courses selected by using purposeful sampling and maximal variation sampling as the strategy. To collect the data, questionnaires were used and an interview was conducted. The collected data were analyzed by using percentage analysis and descriptive analysis. The results of leadership style questionnaire show that the manager 76.7% believes that she applies both autocratic and democratic leadership style while the instructors 66.7% believe that their manager is a democratic. From the interview and open-ended questionnaire for instructors’ teaching performance, it can be explained that under the leadership of the manager, they have a good teaching performance.